Effects of elevated plant selenium levels on reproduction and root-nematode interactions - Prins, Christine N., author; Pilon-Smits, Elizabeth A. H., advisor; Ward, Sarah M., committee member; Bedinger, Patricia A., committee member (Colorado State University. Libraries, 2011)
Selenium is an important element in soils throughout the western United States, and its presence has important consequences for the ecology of these seleniferous sites. Some plants in seleniferous areas have evolved mechanisms to hyperaccumulate Se to 0.1 - 1% of their dry weight. Other plants accumulate moderate Se levels between 0.01 - 0.1% of their dry weight. In the studies described in this thesis, facets of the evolution of Se accumulation and the associated ecology of Se hyperaccumulators are considered. First, I examined the effect of increasing Se on reproductive parameters of Se accumulators and hyperaccumulators. The reproductive parameters were measured through cross-pollinations of greenhouse-grown accumulator plants receiving different Se concentrations. In the accumulator Brassica juncea , increasing Se concentrations in plant tissues caused decreases in biomass, pollen germination, seed weight, seed production, and seed germination. In some cases, however, interactions of similar Se concentrations in both parents actually proved beneficial to reproduction. The hyperaccumulator Stanleya pinnata showed no effect of increased Se concentration on pollen germination. These data provide interesting insight into the potential reproductive cost of Se accumulation, and the apparent evolution of physiological tolerance mechanisms in hyperaccumulators to avoid these reproductive problems. To further investigate the effect of Se on reproduction, S. pinnata plants were taken to a field site with hives of the European honey bee (Apis mellifera) to examine the effect of Se in floral tissues on potential pollinators. The bees and other pollinators showed no preference for or against Se in the flower and foraged on both high- and low-Se plants equally. Because the bees showed no preference, the honey of bees in seleniferous sites was analyzed for the presence of Se, and there were small amounts (up to 2 mg kg-1 FW) of Se found in this honey. These findings are important for bee keepers in seleniferous areas, as they show no evidence of toxic Se levels in their honey and they may even market their honey as Se-enriched and beneficial for human health. The finding that bees do not discriminate between high and low-Se plants does warrant further studies on the potential health effects of the ingested Se on the pollinators and the movement of Se into the food chain. Next, to further investigate the ecology of Se hyperaccumulators, I examined the interactions of hyperaccumulator roots with root-associated nematodes. Selenium hyperaccumulators S. pinnata and Astragalus bisulcatus growing in the field have root Se concentrations between 100 and 1,500 mg Se kg-1 DW, a toxic concentration to most above-ground herbivores. Therefore, it was expected that with increasing root Se concentrations, there would be reduced levels of nematodes associated with plants. There was no significant negative correlation with increasing Se concentration, and even roots containing >1,000 mg Se kg-1 Se harbored nematode herbivores. However, when nematodes extracted from field-harvested plants were used to inoculate greenhouse-grown S. pinnata , plants treated with Se did harbor significantly fewer nematodes several months later. These findings are of significance, both because they suggest the presence of Se-tolerant and potentially Se-specialist nematodes in seleniferous sites, and for the possible use of Se as a pesticide for nematodes in non-seleniferous sites. Furthermore, the roots of hyperaccumulators were examined for the spatial distribution and speciation of Se using X-ray Absorption Spectroscopy (XAS). The majority of the Se was found in the cortex and epidermis of the root, with lower levels in the wood. Organic Se of the C-Se-C type (Se bonded to two carbon atoms, similar to methyl-selenocysteine) was the predominant form of Se in the hyperaccumulator roots, together with a small fraction of inorganic selenite. The findings presented in this thesis may also have relevance for hyperaccumulators of other elements, such as arsenic, cadmium, nickel or zinc, as these metals may also protect roots from nematodes and other root herbivores, and may have similar effects on reproduction. Further investigations may reveal other herbivores that are deterred by root hyperaccumulation, as well as more evidence of specialist herbivores that have evolved tolerance in response to the hyperaccumulator's elemental defense. Beyond insight into the ecological and co-evolutionary relationships between roots and herbivores, the results presented here also have applications in agriculture. Since Se is both a nutrient and a toxin, depending on its concentration, Se could be used as an alternative to organic pesticides in controlling root nematode and herbivore levels in organic and subsistence farming. With careful monitoring, the resulting plants may be considered Se-fortified food with enhanced nutritional value. Finally, the findings presented here provide a framework for follow-up studies investigating the evolution of plant Se hyperaccumulation and the associated effects of (hyper)accumulated plant Se on ecological interactions in seleniferous habitats.
Keywords: hyperaccumulators; selenium; nematodes